PARTISIPASI MASYARAKAT DALAM PROGRAM KAMPUNG TEMATIK DI KAMPUNG BATIK KOTA SEMARANG - Mazidatur - Rohmaniyah; Nunik Retno Herawati; Turtiantoro - - (Journal of Politic and Government Studies, 2023)
Urbanization has a very complex impact on urban life, including poverty and slum settlements. Both of these problems are things that are the responsibility of the government to address. The city of Semarang has a thematic village policy to overcome these problems. In the development of thematic villages, high community participation is required so that the program can run in a sustainable manner, unfortunately the characteristics of urban communities that are individualistic, less familiar with each other, and heterogeneous make community participation in urban areas difficult to carry out. This research uses a qualitative method with a case study type. The results obtained by community participation in the thematic village program in Batik Village have not been optimal because they are still dominated by the Semarang City Government and have not fully involved the community in its development. As a result, the conditions that occur actually disrupt the harmony of society among its citizens